Incorporation of Cyclotriphosphazenes as pendant groups to the sago network - Zainab, Ngaini; Khairul Aidil Azlin, Abd Rahman; Nazlina, Shaari; Hasnain, Hussain; Norhaizat, S; Teng, JX (Malaysian Analytical Sciences Society, 2012)
Cyclotriphosphazene-incorporated sago wastes as pendant groups have been prepared and structurally characterized using FT-IR and SEM. The chemically modified sago wastes composite was applied with binders and developed as sound absorbing panels. These panels are a class of organic-inorganic based materials that exhibit excellent fire retardant properties. Sound absorbance test has given a higher value at 250, 500 and 2000 Hz, which indicates the suitability of the panel for used in medium frequency. The panel was 51% lighter compared to fiberboard. The function and basic manufacturing of sound absorbers products was aligned with the present products in the market.